(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
This research, through the filter of the “health” subject, intends to investigate the interconnection between technology and autonomy in the State-Region relationship. Due to its nature, technique require uniformity of application, affecting the constitutional division of competences and favouring the phenomenon of the centralisation of powers at State level to the detriment of peripheral ones. This phenomenon, which was highlighted during the Covid-19 pandemic, is confirmed with the recovery plan and resilience. The marginal role accorded to territorial representation in the Plan’s governance system, distances the goal of eliminating territorial disparities, which is a necessary condition for the Country’s effective recovery.